Locus-specific Changes in Cell Wall Composition Characteristic of Osmotic Mutants of Neurospora crassa - Livingston, Laura R. (1969)
The osmotic phenotype of Neurospora crassa is characterized by inhibition of growth at high osmolalities of growth medium. Mutations at six osmotic loci of linkage group I were examined to assess the biochemical and physiological effects of these mutants. Isolated cell walls from 23 osmotic strains were compared with the wild type with regard to quantitative levels of the following components: percentage of total dry weight, total glucose, alkali-soluble glucose, nonglucose carbohydrates, amino acids, glucosamine, galactosamine, and a compound tentatively identified as quinovosamine. The last component has not previously been observed in N. crassa cell walls. Although the cell wall dry weight content of osmotic mutants was not altered, walls isolated from all of the osmotic strains had less alkali-insoluble glucose than those from the wild type. In addition, all of the loci except cut exhibited other consistent differences from the wild type. The os-1, os-3, and os-5 mutants had low levels of alkali-soluble glucose. The os-3 and os-5 mutants had high levels of nonglucose carbohydrates, and flm-2 had a low level of nonglucose carbohydrates. The os-4 mutants had low levels of galactosamine and amino acids and high levels alkali-soluble glucose. An os-1 mutant, B135, produced less of the whole alkali-soluble fraction of the cell wall.